2-[(2,4-Dimethylphenyl)iminomethyl]-6-methylphenol - Tanak, Hasan (International Union of Crystallography, 2009)
The title compound, C(16)H(17)NO, is a Schiff base which adopts the phenol–imine tautomeric form in the solid state. The molecule is almost planar, with a dihedral angle of 4.61 (4)° between the aromatic rings. The molecular structure is stabilized by an intramolecular O—H⋯N hydrogen bond which generates a six membered ring.